Sentence-level multi-modal feature learning for depression recognition - Zhang, Guanghua; Zhuo, Guangping; Yang, Yang; Xu, Guohua; Ma, Shukui; Liu, Hao; Ren, Zhiyong (Frontiers in Psychiatry, 2025)
BackgroundThe global prevalence of depression has escalated, exacerbated by societal and economic pressures. Current diagnostic methodologies predominantly utilize single-modality data, which, despite the existence of certain multi-modal strategies, often fail to effectively harness the distinct contributions of each modality in depression detection.MethodsThis study collected multi-modal features from 100 participants (67 depressed patients and 33 non-depressed individuals) to formulate a MMD2023 dataset, and introduces the Sentence-level Multi-modal Feature Learning (SMFL) approach, an automated system designed to enhance depression recognition. SMFL analyzes synchronized sentence-level segments of facial expressions, vocal features, and transcribed texts obtained from patient-doctor interactions. It incorporates Temporal Convolutional Networks (TCN) and Long Short-Term Memory (LSTM) networks to meticulously extract features from each modality, aligned with the structured temporal flow of dialogues. Additionally, the novel Cross-Modal Joint Attention (CMJAT) mechanism is developed to reconcile variances in feature representation across modalities, adeptly adjusting the influence of each modality and amplifying weaker signals to equate with more pronounced features.ResultsValidated on our collected MMD2023 dataset and a public available DAIC-WOZ containing 192 patients dataset, the SMFL achieves accuracies of 91% and 89% respectively, demonstrating superior performance in binary depression classification. This advanced approach not only achieves a higher precision in identifying depression but also ensures a balanced and unified multi-modal feature representation.ConclusionThe SMFL methodology represents a significant advancement in the diagnostic processes of depression, promising a cost-effective, private, and accessible diagnostic tool that aligns with the PHQ-8 clinical standard. By broadening the accessibility of mental health resources, this methodology has the potential to revolutionize the landscape of psychiatric evaluation, augmenting the precision of depression identification and enhancing the overall mental health management infrastructure.